RISK TERRAIN MODELING (RTM) IN THE EVAULATION OF GLOBAL AND LOCAL RISKS - Eşref ERTÜRK (Fırat University, 2019)
Risk evaluation, which has become more complicated in the globalization process, is a necessity that should be applied to a wide range of fields including security, health, environment, economy, and so on. Geography, which has global and local dimensions, has an important place in risk evaluation. Considering place in risk evaluation will help institutions to get efficient and appropriate results. The Risk Terrain Modeling (RTM), which has been developed by the researchers at Rutgers Center on Public Security, is a scientific approach in place-based risk evaluation. In this study, the problem about the negative effects of childhood pneumonia on countries has been evaluated in line with RTM. The significance of similar approaches in security issues has also been discussed. The author argued in the study that all risks related to terrain can be studied through a modeling, thus the prospective problems may be estimated beforehand and the necessary precautions can be determined through this approach.